Prevalence of the germline TP53 p.R337H mutation in families with multiple cases of cancer - Andrade, Kelvin César de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Germline mutations in TP53 gene are associated with Li-Fraumeni syndrome (LFS) and its variants Li-Fraumeni-like (LFL). They predispose carriers to a wide variety of early onset tumors. In Brazil, there is a high frequency of a germline mutation in this gene (NC_000017.9: c.1010G>A; p.R337H) in Southern and Southeastern regions, due to a founder effect. It is estimated to be present in 0,3% ofthe local population, but only few families have been detected. Due to this significant divergence, the purpose of this study was to verify the effectiveness of wider criteria for detection of these individuals. Herein, clinical criteria were established, DNA samples were collected, analyzed by Restriction Fragment Length Polymorphism (RFLP) and sequenced. Thus, assessing the prevalence of this mutation in families with multiple cases of cancer. Based on our proposed criteria, one out of 31 patients (3,22%) was found to carry p.R337H mutation. The patient developed ductal invasive breast cancer at age 47, invasive adenocarcinoma of the lung at age 48 and soft-tissue sarcoma at age 49. In addition, an extensive cancer family history was referred, atypical for LFS, including a case of Ewing’s sarcoma. These outcomes indicate that the proposed criteria may detect probable carriers who did not fit previous LFS criteria. Nevertheless, additional studies, which might include a larger number of families and more stringent parameters, will be useful to improve screening sensibility
Prevalence of the germline TP53 p.R337H mutation in families with multiple cases of cancer
Keywords: Câncer - Tratamento; Genes; Mutagenese; Oncologia; Mutagenesis